Response of Ti microstructure in mechanical and laser forming processes - Fidder, H.; Ocelík, V.; Botes, A.; De Hosson, J. T. M. (Journal of materials science, 2018)
Microstructural deformation mechanisms present during three different forming processes in commercially pure Ti were analysed. Room temperature mechanical forming, laser beam forming and a combination of these two processes were applied to thick metal plates in order to achieve the same final shape. An electron backscatter diffraction technique was used to study the plate microstructure before and after applying the forming processes. Substantial differences among the main deformation mechanisms were clearly detected. In pure mechanical forming at room temperature, mechanical twinning predominates in both compression and tensile areas. A dislocation slip mechanism inside the compression and tensile area is characteristic of the pure laser forming process. Forming processes which subsequently combine the laser and mechanical approaches result in a combination of twinning and dislocation mechanisms. The Schmid factor at an individual grain level, the local temperature and the strain rate are factors that determine which deformation mechanism will prevail at the microscopic level. The final microstructures obtained after the different forming processes were applied are discussed from the point of view of their influence on the performance of the resulting formed product. The observations suggest that phase transformation in Ti is an additional microstructural factor that has to be considered during laser forming.